Critique of the Critical Period Hypothesis in second language acquisition: Literature review - Hrubý, Jan (Univerzita Pardubice, 2024)
The thesis focuses on the critique of the Critical Period Hypothesis in second language acquisition. The theoretical part defines the core concepts of both the second language acquisition and the Critical Period Hypothesis through the method of a historical overview. The practical part aims to review studies which provide results contradicting parts of the Critical Period Hypothesis.
Kritika hypotézy kritického období osvojování cizího jazyka: přehledová studie
Keywords: osvojování cizích jazyků; kritická perioda; věk osvojení cizího jazyka; second language acquisition; critical period; age of acquisition